2021
DOI: 10.3389/frai.2021.681174
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Machine Learning Methods for Persistence Diagrams

Abstract: Many and varied methods currently exist for featurization, which is the process of mapping persistence diagrams to Euclidean space, with the goal of maximally preserving structure. However, and to our knowledge, there are presently no methodical comparisons of existing approaches, nor a standardized collection of test data sets. This paper provides a comparative study of several such methods. In particular, we review, evaluate, and compare the stable multi-scale kernel, persistence landscapes, persistence imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Filling this gap will require filtration algorithms that consider additional information such as the nature and the physicochemical features of amino acids, which represents a promising direction for the future development of topological analysis in phylogenetics. Finally, another line of research is exploring the potential contribution of approaches combining PH with machine learning to study protein structure evolution, as PH has been shown to significantly improve classical machine learning ( 89 , 90 ). Indeed, PH-descriptors provide vectorizations of the complex geometry of protein structures, facilitating the application of learning methods.…”
Section: Discussionmentioning
confidence: 99%
“…Filling this gap will require filtration algorithms that consider additional information such as the nature and the physicochemical features of amino acids, which represents a promising direction for the future development of topological analysis in phylogenetics. Finally, another line of research is exploring the potential contribution of approaches combining PH with machine learning to study protein structure evolution, as PH has been shown to significantly improve classical machine learning ( 89 , 90 ). Indeed, PH-descriptors provide vectorizations of the complex geometry of protein structures, facilitating the application of learning methods.…”
Section: Discussionmentioning
confidence: 99%
“…We use persistence landscapes 7 to convert persistence diagrams into vectors, which are then used for machine learning. There are many other ways to do this 41 and each of these may be used with our method in place of persistence landscapes. We chose persistence landscapes for two advantages.…”
Section: Methodsmentioning
confidence: 99%
“…This cropping value (i.e., the filtration value) is systematically varied from the lowest to the highest values of the image, or vice versa, thus generating a different subspace for each value. As a result, the persistence homology analysis captures and examines the evolution of topological features across different thresholds, enabling insights into the structural properties of the image at various scales (Barnes et al 2021).…”
Section: Persistent Homologymentioning
confidence: 99%